2012
DOI: 10.5194/bg-9-1845-2012
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of carbon dioxide emissions from fossil-fuel combustion

Abstract: Abstract. This synthesis discusses the emissions of carbon dioxide from fossil-fuel combustion and cement production. While much is known about these emissions, there is still much that is unknown about the details surrounding these emissions. This synthesis explores our knowledge of these emissions in terms of why there is concern about them; how they are calculated; the major global efforts on inventorying them; their global, regional, and national totals at different spatial and temporal scales; how they ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
316
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(349 citation statements)
references
References 75 publications
(112 reference statements)
17
316
0
2
Order By: Relevance
“…The use of population alone as a proxy to infer the air pollution level is under debate (Alpert et al, 2005;Ramanathan et al, 2007;Alpert and Kishcha, 2008;Stanhill and Cohen, 2009;Imamovic et al, 2016). Related are issues associated with the use of population-based proxies to infer CO 2 emissions (for an overview, see Andres et al, 2012), even though CO 2 emissions are not necessar- Around 1955-1960Around 1975-1980Around 1995-2000 Akita Fukuoka Kagoshima 1957 (1) 1977 (1) 1996 (1) 1957 (2) 1977 (2) 1999 (1) 1954 (2) 1977 ( 13979 Around 1955-1960Around 1975-1980Around 1995-2000 Matsumoto Naha Sapporo 1959 (1) 1976 (1) 1995 (1) 1962 (2) 1977 (2) 1997 (1) 1958 (1) 1977 ( Figure 5. Chronological changes in land use surrounding the current and previous sites for the 14 observatories under study (length of the scale bar is 1 km).…”
Section: Data Related To Urbanizationmentioning
confidence: 99%
“…The use of population alone as a proxy to infer the air pollution level is under debate (Alpert et al, 2005;Ramanathan et al, 2007;Alpert and Kishcha, 2008;Stanhill and Cohen, 2009;Imamovic et al, 2016). Related are issues associated with the use of population-based proxies to infer CO 2 emissions (for an overview, see Andres et al, 2012), even though CO 2 emissions are not necessar- Around 1955-1960Around 1975-1980Around 1995-2000 Akita Fukuoka Kagoshima 1957 (1) 1977 (1) 1996 (1) 1957 (2) 1977 (2) 1999 (1) 1954 (2) 1977 ( 13979 Around 1955-1960Around 1975-1980Around 1995-2000 Matsumoto Naha Sapporo 1959 (1) 1976 (1) 1995 (1) 1962 (2) 1977 (2) 1997 (1) 1958 (1) 1977 ( Figure 5. Chronological changes in land use surrounding the current and previous sites for the 14 observatories under study (length of the scale bar is 1 km).…”
Section: Data Related To Urbanizationmentioning
confidence: 99%
“…Pregger et al (2007) showed that two 0.5 • inventories for Western Europe, for 2003, differed at the grid-cell level by 20 %, with a standard deviation of 40 %; at finer resolutions, the disagreement worsened. Sources of errors in inventories are discussed in detail in Andres et al (2012), Raupach et al (2009) and Rayner et al (2010). These uncertainties lead to frequent corrections of sub-national inventories of combustion products (Streets et al, 2006) and model predictions of CO 2 concentrations that disagree with observations locally (Brioude et al, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…ffCO 2 emissions are the largest net carbon flux at the atmosphere-surface interface (Friedlingstein et al, 2006) and spatially disaggregated (or gridded) ffCO 2 emissions form a critical input into general circulation and integrated assessment models (Andres et al, 2012). An understanding of fossil-fuel emissions is clearly necessary for characterizing the anthropogenic climate impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the total amount of anthropogenic CO 2 emissions can be estimated by relatively well-documented global fuelconsumption data with a small degree of uncertainty (Boden et al, 2011), and the uncertainties involved in the total amount of anthropogenic CO 2 emissions are much smaller than those related to natural emissions. However, their spatial distribution, strength and temporal development still remain elusive because of their inherent non-uniformities (Andres et al, 2012;Gurney et al, 2009). Marland (2008 pointed out that even a tiny amount of uncertainty, i.e.…”
Section: Z Peng Et Al: a Regional Carbon Data Assimilation Systemmentioning
confidence: 99%